Short Stature is Progressive in Patients with Heterozygous NPR2 Mutations - Hanley, Patrick C (J Clin Endocrinol Metab, 2020)
BACKGROUND: NPR2 encodes atrial natriuretic peptide receptor B (ANPRB), a regulator of skeletal growth. Biallelic loss-of-function mutations in NPR2 result in acromesomelic dysplasia Maroteaux type (AMDM; OMIM 602875), while heterozygous mutations may account for 2% to 6% of idiopathic short stature (ISS). OBJECTIVE: Describe the physical proportions and growth characteristics of an extended family with novel NPR2 mutations including members with AMDM, ISS, or normal stature. DESIGN AND PARTICIPANTS: We performed whole exome sequencing in 2 healthy parents and 2 children with AMDM. Detailed genotyping and phenotyping were performed on members of a multigenerational family in an academic medical center. We expressed mutant proteins in mammalian cells and characterized expression and function. RESULTS: The sisters with AMDM were compound heterozygotes for missense mutations in the NPR2 gene, a novel p.P93S (maternal) and the previously reported p.R989L (paternal). Both mutant ANPRB proteins were normally expressed in HEK293T cells and exhibited dominant negative effects on wild-type ANPRB catalytic activity. Heterozygous relatives had proportionate short stature (height z-scores −2.06 ± 0.97, median ± SD) compared with their wild-type siblings (−1.37 ± 0.59). Height z-scores progressively and significantly decreased as NPR2-heterozygous children matured, while remaining constant in their wild-type siblings. CONCLUSIONS: Biallelic NPR2 mutations cause severe skeletal dysplasia (AMDM), whereas heterozygous mutations lead to a subtler phenotype characterized by progressive short stature with by increasing loss of height potential with age.